Pergeseran dan Mitigasi Risiko Keuangan dalam Subsidi Pupuk: Kajian Kebijakan Bisnis dan Kebijakan Publik - Sunarto, Hari (Jurnal Aplikasi Manajemen, 2011)
This study examines the financial risks exposure among three main stakeholders i.e. fertilizer producers, the government of Indonesia and farmers due to changes in fertilizer subsidy policies. The fertilizer subsidy started in 1971, but there have been some policy changes in term of three cancelations and resumption, changes in the mode of subsidy payments i.e. from natural gas (input) subsidy to fertilizer price (output) subsidy. The switching subsidy policies imply shifting of financial risks among stakeholders. Smart financial managers of Pusri Group had shifted the financial risk to the Government of Indonesia since 2007. The gas subsidy replaced by the price subsidy, that is the difference between cost of good sold (CGS) and fertilizer ceiling price (HET). The CGS is volatile and increasing over time, while the HET is a rigid in nature. The price subsidy lead to a sharp increase in total subsidy born by Government of Indonesia.